Betaines and related ammonium compounds in chestnut (Castanea sativa Mill.). (1st April 2016) - Servillo, Luigi; Giovane, Alfonso; Casale, Rosario; Balestrieri, Maria Luisa; Cautela, Domenico; Paolucci, Marina; Siano, Francesco; Volpe, Maria Grazia; Castaldo, Domenico
Highlights: Betaines in fruits and flours of Italian chestnuts were quantified. Stachydrine and N-methylproline were detected for the first time in chestnut. β-Alanine betaine was detected for the first time in chestnut. Three pipecolic acid derivatives were detected for the first time in chestnut. The mass spectrometric features of the above derivatives were reported. Abstract: Chestnut fruits, being poor of simple sugars and consisting mainly of fibers and starch, are among the constituents of Mediterranean diet. While numerous studies report on content of proteins and amino acids in chestnut, no one has appeared so far on betaines, an important class of nitrogen compounds ubiquitous in plants for their protective action in response to abiotic stress. In this study, we analyzed by HPLC–ESI-tandem mass spectrometry, in fruits and flours of varieties of chestnut cultivated in Italy, the composition of betaines and ammonium compounds intermediates of their biosynthesis. Besides the parent amino acids, the compounds quantified were choline, glycerophosphocholine, phosphocholine, glycine betaine, N -methylproline, proline betaine (stachydrine), β-alanine betaine, 4-guanidinobutyric acid, trigonelline, N, N, N -trimethyllysine. Interestingly, some uncommon derivatives of pipecolic acid, such as N -methylpipecolic acid, 4-hydroxypipecolic acid and 4-hydroxy- N -methylpipecolic acid were identified for the first time in chestnut samples and characterized by MS n tandem mass spectrometry.